Employee well-being and employee retention: empirical study in an Indonesian company - Hendri Ardianto; Gunawan Gusnadi; Indra Dharma; Datu Razali Datu Eranza; Do Huu Nguyen Loc (Ifma Publishing, 2025)
This study aims to examine the influence of employee well-being on employee retention. A quantitative survey method was employed to collect data from 154 employees out of a population of 250 in an agricultural product processing company. A five-point Likert-scale questionnaire, validated and tested for reliability, served as the primary instrument for data collection. The data were analyzed using descriptive and inferential statistics, including simple linear regression at a 0.05 significance level using SPSS version 24.0. The results revealed a significant and positive relationship between employee well-being and retention. Employees who experience a higher sense of well-being are likelier to remain with the company. Furthermore, longer tenure is associated with more stable levels of well-being and retention. These findings underscore the importance of prioritizing employee well-being as a strategic approach to fostering loyalty and minimizing turnover. Targeted managerial interventions, particularly during critical tenure periods, are essential for cultivating a sustainable and healthy work environment.